Species reassessment congruent with the phylogeographical study of the Biston falcata species group. (22nd April 2019) - Cheng, Rui; Jiang, Nan; Xue, Dayong; Han, Hongxiang
Abstract: The Himalaya, Hengduan, and Qinling mountains are very important mountain systems in China. Because they are geographically adjacent, species distributed in these three mountains usually have close relationships, but species/populations distributed in the first two mountain systems have higher genetic diversity and more complex phylogenetic structures than those found in the Qinling Mountains. In this study, we used molecular and morphological methods to explore the phylogeographical structure, species differentiation, and evolutionary history of the Biston falcata species group, which is widely distributed in the Himalaya, Hengduan, and Qinling mountains. Five species were identified; B. quercii is distributed in the Qinling Mountains and its adjacent areas, and the other four species are mainly distributed in the Himalaya and Hengduan Mountains. Four gradual species differentiation events occurred at approximately 3.07, 1.75, 1.50, and 1.30 Ma, corresponding to the stage with strong geological movements of the Qinghai‐Tibet Plateau. The low land between the Qinling and the northern Hengduan Mountains, the Sichuan Basin, the low land between the eastern and central Himalaya Mountains and the Mekong‐Salween Divide are four geographical barriers that resulted in multiple speciations. In addition, long‐range dispersal as another mechanism for speciation is non‐negligible. In spite of failing to confirm the ancestral area, our study provided direct evidence of the speciation induced by the geographical barriers and adaptation to the plateau. Abstract : Five species were identified within the Biston falcata species group. Four geographical barriers that resulted in multiple speciations were supported. The Qinling Mountains are the possible ancestral area of the B. falcata species group.